Designing and fabricating the punch chuck and precision hole punch diameter 3.0mm, 3.5mm and 4.0mm for turret punch machine - Prabagar, Murukesavan (2008)
Design and fabricating the punch chuck and precision hole punch 3.0mm, 3.5mm and 4.0mm is a conceptual understanding of manufacturing engineering which is not provided in daily lectures room due to the fact that it is advance knowledge in this field. The project is to test and analyze the percentage of failure of punch tool fabricated using mild steel during punching process. As such, it is vital to attain this basic knowledge through this project. The purpose of this project is to design and fabricate the punch chuck and precision hole punch 3.0mm, 3.5mm and 4.0mm. The design must follow the dimensions of the original punch tool so that it could be mounted into the machine. A material test should be done to determine the hardness of mild steel before fabrication. The progress of this project needs documenting, as it can be a good reference for the next student who involve in this project as well as for a research related to the punch tool. This report describes the project development of the first prototype of punch chuck and precision hole punch fabricated using mild steel material.